Dysbiosis of the Vaginal Microbiota and Higher Vaginal Kynurenine/Tryptophan Ratio Reveals an Association with Chlamydia trachomatis Genital Infections - Ziklo, Noa; Vidgen, Miranda E.; Taing, Kuong; Huston, Wilhelmina M.; Timms, Peter (Frontiers in Cellular and Infection Microbiology, 2018)
The natural course of Chlamydia trachomatis urogenital tract infections varies between individuals. While protective immunity can occur, some women can become reinfected, contributing to the development of severe pathology. While the reasons for these differences are unknown, an individual’s response to induced interferon-γ (IFN-γ) is suggested to be critical. IFN-γ induction of the enzyme indoleamine 2,3-dioxygenase, which depletes tryptophan, may be the key. One hypothesis suggests that indole-producing bacteria in the vaginal microbiota can provide a substrate for the Chlamydia to synthesize tryptophan, rescuing the Chlamydia from host IFN-γ attack. We studied a cohort of 25 women who were either, Chlamydia negative, Chlamydia positive with a single infection, or Chlamydia positive with repeated infection, to test our hypothesis. We characterized their vaginal microbiota, cytokine response, as well as their tryptophan, kynurenine and indole concentrations directly in vaginal secretions. We found that C. trachomatis urogenital tract infections either initial or repeat infections, were associated with elevated vaginal kynurenine/tryptophan ratios, primarily as a result of elevated kynurenine levels. In addition, vaginal microbiota of community state type (CST) IV showed significantly lower vaginal tryptophan levels compared to CST I and III, which might be related to a higher abundance of indole producers found within this group. Furthermore, we found a higher abundance of indole producers in women who cleared their Chlamydia infection post antibiotic treatment. This study demonstrates for the first time in vivo, the association between high vaginal kynurenine/tryptophan ratios and C. trachomatis infections. In addition, tryptophan depletion was associated with vaginal microbiota of CST IV